Chimerism of allogeneic mesenchymal cells in bone marrow, liver, and spleen after mesenchymal stem cells infusion. (27th October 2013) - Meleshko, Alexander; Prakharenia, Irina; Kletski, Semen; Isaikina, Yanina
Abstract: Although an infusion of culture‐expanded MSCs is applied in clinic to improve results of HSCs transplantation and for a treatment of musculoskeletal disorders, homing, and engraftment potential of culture‐expanded MSC in humans is still obscure. We report two female patients who received allogeneic BM transplantation as a treatment of hematological diseases and a transplantation of MSCs from third‐party male donors. Both patients died within one yr of infectious complications. Specimens of paraffin‐embedded blocks of tissues from transplanted patients were taken. The aim of the study was to estimate possible homing and engraftment of allogeneic BM‐derived MSCs in some tissues/organs of recipient. Sensitive real‐time quantitative PCR analysis was applied with SRY gene as a target. MSC chimerism was found in BM, liver, and spleen of both patients. We conclude that sensitive RQ‐PCR analysis is acceptable for low‐level chimerism evaluation even in paraffin‐embedded tissue specimens.